Democratic Fatigue in Indonesia: The Anomaly of Jokowi's Approval Rating Amidst Democratic Regression - Latief, Azhari M; Nasution, M. Arif; Ginting, Bengkel (Journal Public Policy, 2024)
Drawing insights from the evolution of political discourse in Indonesia since the reformation era, it becomes evident that democracy plays a pivotal role in underpinning the continuity of national leadership. The quality of democracy stands as a decisive factor in shaping public endorsement towards leaders. As the quality of democracy diminishes during a leader's tenure, the likelihood of rejection by the populace amplifies. However, an anomaly surfaces when assessing the leadership tenure of Jokowi. Despite a regression in democratic standards under his stewardship, Jokowi garnered a remarkably high approval rating. This article endeavors to elucidate this anomaly through the lens of psychoanalysis. Departing from prevailing research contentions that perceive media techniques as instrumental in augmenting approval ratings through hegemonic manipulation, this study delves into probing why the public places trust in the media as a hegemonic instrument. Employing qualitative methodologies and grounded within an interpretive framework utilizing secondary sources, this article asserts that the Indonesian public, afflicted by trauma and disillusionment towards democracy, gravitates towards objects of desire imbued with non-democratic values. It posits that fluctuations in approval ratings are not contingent upon the quality of democracy but are rather influenced by the efficacy of power in navigating desires and meeting the needs that ensure subject stability. Within this discourse, the democratic regression witnessed during Jokowi's tenure seemingly succeeded in assuaging the populace's anxieties regarding their sense of completeness, encompassing uncertainties, the dearth of political party representation, identity crises, and leadership presence. Consequently, this phenomenon not only engenders satisfaction among the populace but also fosters acceptance of Jokowi's presidential actions and policies, thereby bolstering his political stature.